Сторінки з біографії Дмитра Білика – колишнього директора гончарної школи в Опішному - Міщанин, В. (Сiверянський лiтопис, 2018)
У статті на основі архівних матеріалів та спогадів родичів висвітлено окремі сторінки з біографії Дмитра Аврамовича Білика (1894 – друга половина 1940-х (?) – директора гончарної школи в столиці українського гончарства Опішному середини 1920-х років. В статье, на основе архивных материалов и воспоминаний родственников, изложены отдельные страницы из биографии Дмитрия Аврамовича Билыка (1894 – вторая половина 1940-х (?) – директора гончарной школы в Опишному средины 1920-х годов. The paper deals with archival materials, the memoirs of the daughter and relatives which cover some pages of the biography of Dmytro Avramovych Bilyk (1894 – the second half of the 1940s (?)) which was the director of the potter’s school in the capital of Ukrainian pottery in Opishne in the middle of the 1920s. His name, as the names of other repressed workers of the potter’s educational institutions of Opishne in the 1920’s and 1930’s, was removed out of the history of Opishne pottery for more than half a century. Dmytro Bilyk was a native opishnian, the son of a local carpenter. He fought on the fronts of the World War I. After returning home, in 1919 he fought for Soviet power in a partisan detachment under the command of his one-party Left SRs Timothy Kocherga. In the 1930s he worked as a teacher of mathematics at a local school. In 1937, as a former Left SR he was arrested and sentenced. Punishment served in Kharkiv. In 1942, at the time of the German occupation of Opishne, he returned to the town where he worked as the head of the department of education of the Opishnya district. In the fall of 1943 he was in the Red Army. There is evidence that he was in German captivity, and that he was killed at the front. However, the indisputable fact is that he lived in Opishne after the War, where during the period from August 1945 to February 1946 he worked as an accountant at the Zinkivsky District Education Department. Worthy of note is the fact that he was dismissed from his work by order of the Opishna District Executive Committee. This gives grounds to say that the dismissal was due to his former Left SRs activities. After all, in the postwar years there was another wave of repressions, particularly in Opishne, against the former Left SRs. Dmytrо Bilyk, obviously fleeing from arrest, traveled to Western Ukraine in 1947, where his life suppously ended tragically. In the biography of Dmytrо Bilyk there are still a lot of unknown and confusing pages.